As "transformações" no espaço rural e a atuação da Pedagogia da Alternância no município de Rio Novo do Sul-ES - Moro, Ildranis Laquini (2015)
This study aims to analyze the changes occurred in rural area of the municipality of Rio Novo do Sul-ES, interweaving with the performance of the education system mediated by the Pedagogy of Alternation, with which this city is contemplated, establishing a parallel between the 60s and the present day, which points out that rural life is changing, so looking for the contemporary rural initially requires you to watch out for its diversity, from which emerge possibilities and simultaneously concerns, considering the new functions that will be consolidated and incorporated on reproduction strategies of many of the families who inhabit this area. This work emphasizes the Pedagogy of Alternation, considering its performance through the dynamics of rural areas. To achieve the proposed objective, we outlined a work plan which first sought to conduct a bibliographic reading and discussion, aiming both theoretical understanding of the historicity of the Pedagogy of Alternation as agrarian context of the study, discussing family farming and pluriactivity, emphasizing the issue of youth and education in the countryside. Then, there was a survey of indicators of space to understand the rural dynamics, emphasizing some data on rural and urban population of the Espírito Santo and the municipality of Rio Novo do Sul. To collect data, it proceeded to the field research, which sought people linked to the foundation of the Agricultural Family School of Rio Novo do Sul and MEPES and leaders of rural communities of Rio Novo do Sul, as well as some former students of the Agricultural Family School, allowing interweaving, then, the theoretical debate with empirical issues gathered. Among the results, there is the need of reframing the Agricultural Family School in the city and arouse a new look for the contemporary rural.